Dynamics of fuel in tanks - Addington, J. W. (College of Aeronautics, 1960)
The validity of the available theory in determining the natural frequency of the fundamental fuel sloshing mode in a rectangular tank was experimentally investigated. The results were found to agree within 5% over the whole range, end were quite accurate in the extreme "shallow and deep water" regions. A. qualitative investigation into baffle types and positioning indicates that baffles should be positioned in a region of highest velocity such that the surface waves are trapped and the energy dissipated at the shallowest depth possible, This suggests that, for a tank with varying liquid depth, a multi-perforated baffle should be employed. A total orifice area of one quarter the baffle area is suggested.